Modeling of the HERMES submillimeter source lensed by a dark matter dominated foreground group of galaxies - Gavazzi, R.; Cooray, A.; Conley, A.; Aguirre, J.; Amblard, A.; Auld, R.; Beelen, A.; Blain, A.; Blundell, R.; Bock, J.; Bradford, C.; Bridge, C.; et al. (2011)
We present the results of a gravitational lensing analysis of the bright z s = 2.957 submillimeter galaxy (SMG) HERMES found in the Herschel/SPIRE science demonstration phase data from the Herschel Multi-tiered Extragalactic Survey (HerMES) project. The high-resolution imaging available in optical and near-IR channels, along with CO emission obtained with the Plateau de Bure Interferometer, allows us to precisely estimate the intrinsic source extension and hence estimate the total lensing magnification to be μ = 10.9 ± 0.7. We measure the half-light radius R eff of the source in the rest-frame near-UV and V bands that characterize the unobscured light coming from stars and find R eff, * = [2.0 ± 0.1] kpc, in good agreement with recent studies on the SMG population. This lens model is also used to estimate the size of the gas distribution (R eff, gas = [1.1 ± 0.5] kpc) by mapping back in the source plane the CO (J = 5 → 4) transition line emission. The lens modeling yields a relatively large Einstein radius R Ein = 4 10 ± 0 02, corresponding to a deflector velocity dispersion of [483 ± 16] km s–1. This shows that HERMES is lensed by a galaxy group-size dark matter halo at redshift z l ~ 0.6. The projected dark matter contribution largely dominates the mass budget within the Einstein radius with f dm(< R Ein) ~ 80%. This fraction reduces to f dm(< R eff, G1 4.5 kpc) ~ 47% within the effective radius of the main deflecting galaxy of stellar mass M *, G1 = [8.5 ± 1.6] × 1011 M ☉. At this smaller scale the dark matter fraction is consistent with results already found for massive lensing ellipticals at z ~ 0.2 from the Sloan Lens ACS Survey.